Dielectric waveguide bending adapter with ideal transmission : practical design strategy of area-preserving affine transformation optics - Xu, Hongyi (2012)
Transformation optics has inspired numerous conceptual devices since the first theoretical model of invisibility cloaks. However, the transition of these concepts into industrial applications is now widely acknowledged as a challenging bottleneck. A practical design strategy that can be adopted by industrial engineers is thus desirable at this stage. Here we propose an integrated design strategy imposing practical constraints on the area-preserving affine coordinate transformation as a general practical method to solve the problem of nonmagnetism. Practical concerns related to fabrication, such as anisotropy degree and bending angles, serve as additional constraints to the transformation. As a specific example, we illustrate how to apply this practical strategy to the design of a two-dimensional electromagnetic waveguide bending adapter. Our study is a significant step toward practical use of ideal transformation optics devices that can be implemented with natural dielectric materials.